Picosecond precision time‐of‐flight digital converter - G. Wieczorek; W. Oliwa (Electronics Letters)
Time‐of‐flight (TOF) digital converter implemented in field programmable gate array has been introduced. The operation is based on train of pulses transmission and counting received pulses in bank of counters. The bank of counters clock signal and the transmitted pulses clock signal are slightly different in frequency. This small difference is a key factor for the measurement method and is achieved by phase locked loop. TOF for the transmitted pulses is directly calculated upon counters counts. Time interval resolution for the prototype instrument is 10.4 ps and average RMS uncertainty value is 12.3 ps. There is no need for special calibration. TOF digital converter requires minimum amount of resources and is suitable for low‐cost applications.